2002
DOI: 10.4049/jimmunol.169.5.2323
|View full text |Cite
|
Sign up to set email alerts
|

Murine Malaria Is Exacerbated by CTLA-4 Blockade

Abstract: Cytolytic T lymphocyte-associated Ag-4 (CD152) is a negatively regulating molecule, which is primarily expressed on T cells following their activation. In this study, we have examined the role of CTLA-4 expression in experimental blood-stage malaria. Similar to human malaria, CTLA-4 is expressed on CD4+ T cells of C57BL/6 mice after infection with Plasmodium berghei. A kinetic analysis revealed that CTLA-4 expression was increased on day 5 postinfection and reached a peak on day 9 postinfection, when almost 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 45 publications
7
66
2
1
Order By: Relevance
“…found that blockade of CTLA-4 led to enhanced immune pathology triggered by T cells producing proinflammatory cytokines (13,14). This supports the idea that the rapid induction of CTLA-4 during the blood stage of a PbA infection is a means to counterregulate the strong and polarized activation of the TH1 arm of the immune system to prevent immune pathology.…”
supporting
confidence: 70%
“…found that blockade of CTLA-4 led to enhanced immune pathology triggered by T cells producing proinflammatory cytokines (13,14). This supports the idea that the rapid induction of CTLA-4 during the blood stage of a PbA infection is a means to counterregulate the strong and polarized activation of the TH1 arm of the immune system to prevent immune pathology.…”
supporting
confidence: 70%
“…Several studies have shown that during experimental malaria infection different regulatory mechanisms are triggered to avoid overwhelming pathology, such as production of IL-10 and TGF-ß (35,36). We have found that the negative costimulators CTLA-4 and BTLA expressed on T cells play a critical role during PbA infection by dampening the immune response (11)(12)(13). Recently, it was found that CTLA-4 is not only expressed by Foxp3 ϩ T reg constitutively, but is also critical for their function (37).…”
Section: Discussionmentioning
confidence: 79%
“…In light of the present study and our previous work, in which we demonstrate that during experimental malaria many more cells are CTLA-4 ϩ CD4 ϩ Foxp3 Ϫ T cells than CD4 ϩ Foxp3 ϩ T reg , it is tempting to speculate that counterregulatory mechanisms on activated T eff such as CTLA-4 induction represent a more suitable mechanism to control a rapidly evolving pathology (11,38). However, we cannot exclude the possibility that the exacerbation of pathology by anti-CTLA-4 treatment during PbA malaria (11,12) is a consequence of a functional restriction of CTLA-4 on both activated T eff and T reg .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…CTLA-4-positive cells are elevated in acute P. falciparum and vivax malarias in humans [66][67][68]. Murine malaria is exacerbated by a CTLA-4 blockade, which induces higher parasitemia than in controls [69][70][71]. These findings suggest that CTLA-4 expression restricts pathogen-specific T-cell responses in malaria.…”
Section: The Genomic Factors Associated With Vitamin D In Malariamentioning
confidence: 61%